Evaluation of Serum Lipid Associated Sialic Acid (LASA) Concentration, Malonaldehyde Determination and Some Biochemical Parameters in Arteriosclerosis Patients. - Hussein, Jian L.; Mohammad Saheed, Najat Z. (Science Journal of University of Zakho, 2015)
The present study was carried out to evaluate the level Lipid associated Sialic Acid (LASA) in patients with cardiovascular Atherosclerosis disease. The study includes three groups the first those who conducted the operation of heart catheter, the second who prepared to enter for catheterizing operation they didn’t conducted Catheter operations for them before, while the last group are the normal persons control. The data analysis reflects a significant increase serum LASA level in the patients when compared to normal controls (P< 0.0001) for the both patients groups which were done operation catheterize and those are prepared to enter the catheterize. As will as there were shows high significant coloration relation of LASA with some biochemical parameter such as (Bilirubin, HbA1C, thyroxine T4 and CK-MB).